Longitudinal associations between albuminuria and renal function and annual brain volume changes: the Ohasama study - Shingo Nakayama; Michihiro Satoh; Satoshi Yamaguchi; Ayana Saito; Hiroki Nobayashi; Megumi Tsubota-Utsugi; Yukako Tatsumi; Takahisa Murakami; Takahito Yagihashi; Maya Toyama; Takuo Hirose; Azusa Hara; et al. (Clinical and Experimental Nephrology, 2026)
Abstract Background Longitudinal studies have not examined the associations between albuminuria and renal function and changes in brain volume. Therefore, we investigated it in a general Asian population after excluding individuals with antihypertensive medication use and accounting for loss to follow-up bias. Methods We analyzed data from 114 participants aged ≥ 50 years without a history of ischemic heart disease, stroke, or antihypertensive treatment in Ohasama town, Japan. Brain volumes were measured using magnetic resonance imaging. Multiple linear regression was performed to assess the associations between urinary albumin-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) and annual symmetric percentage change (ASPC) in brain volume after adjusting for covariates. Dropout bias was adjusted using inverse probability weighting (IPW). Results The mean age of participants was 66.9 years, 72.8% of whom were women, and the mean follow-up period was 4.78 years. After IPW, high UACR was associated with ASPCs in the frontal lobe (standardized regression coefficient [β] = − 0.24, 95% confidence interval [CI] = − 0.43 to − 0.056, P = 0.011), cingulate gyrus (β = − 0.18, 95% CI = − 0.35 to − 0.0081, P = 0.040), parahippocampal gyrus (β = − 0.20, 95% CI = − 0.38 to − 0.026, P = 0.025), and insula (β = − 0.19, 95% CI = − 0.37 to − 0.018, P = 0.031), and eGFR was not associated with ASPCs in any brain region. However, these associations did not remain significant after correction for multiple comparisons. Conclusion We found associations between albuminuria and volume decline in the frontal lobe, cingulate gyrus, parahippocampal gyrus, and insula. Albuminuria may be associated with regional brain volume decline.